Chromosomal Mutagenesis - Pruett-Miller, Shondra M.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Humana, 2015)
This new edition explores current and emerging mutagenesis methods focusing specifically on mammalian systems and commonly used model organisms through comprehensive coverage and detailed protocols. Since the first edition, major advances and discoveries have made chromosomal mutagenesis a widely used technique and one that is available to any molecular biology laboratory, and this collection provides detailed protocols, case-studies, and reviews from thought-leaders in the field. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Authoritative and fully updated, Chromosomal Mutagenesis, Second Edition aims to help speed scientific discovery and aid in the next advances in the field.
Genome Editing by Targeted Chromosomal Mutagenesis -- piggyBac Transposon-Based Insertional Mutagenesis in Mouse Haploid Embryonic Stem Cells -- Using Phage Integrases in a Site-Specific Dual Integrase Cassette Exchange Strategy -- Genome Mutagenesis Using Synthetic Triplex-Forming Molecules and Recombinagenic DNA -- Genome Engineering Using Adeno-Associated Virus (AAV) -- Engineering of Customized Meganucleases Via In Vitro Compartmentalization and In Cellulo Optimization -- Efficient Design and Assembly of Custom TALENs Using the Golden Gate Platform -- Ligation-Independent Cloning (LIC) Assembly of TALENs -- Assembly and Characterization of megaTALs for Hyperspecific Genome Engineering Applications -- Genome Engineering Using CRISPR-Cas9 System -- Donor Plasmid Design for Codon and Single Base Genome Editing Using Zinc Finger Nucleases -- Endogenous Gene Tagging with Fluorescent Proteins -- Silencing Long Non-Coding RNAs with Genome-Editing Tools -- Gene Editing Using ssODNs with Engineered Endonucleases -- Genome Editing in Human Pluripotent Stem Cells Using Site-Specific Nucleases -- Strategies to Increase Genome Editing Frequencies and to Facilitate the Identification of Edited Cells -- Using Engineered Endonucleases to Create Knockout and Knockin Zebrafish Models -- Creating Knockout and Knockin Rodents Using Engineered Endonucleases Via Direct Embryo Injection -- Simple Sperm Preservation by Freeze-Drying for Conserving Animal Strains.
Keywords: Human genetics; Genetic engineering; Human Genetics; Genetic Engineering